Peace operations and organised crime : enemies or allies? - Cockayne, James; Lupel, Adam (Routledge, 2011)
Peace operations are increasingly on the front line in the international community's fight against organized crime; this book explores how, in some cases, peace operations and organized crime are clear enemies, while in others, they may become tacit allies.